Climate Resilient Ningbo Project : Local Resilience Action Plan, Volume 2. Appendices - World Bank (Washington, DC, 2013)
Ningbo serves as the Chinese pilot city for the World Bank Climate Resilient Cities (CRC) Program. The CRC program aims to, prepare local governments in the East Asia region to better understand the concepts and consequences of climate change; how climate change consequences contribute to urban vulnerabilities; and what is being done by city governments in East Asia and around the world to actively engage in learning capacity building, and capital investment programs for building sustainable, resilient communities. This local resilience action plan (LRAP) had four parts. Part one investigated natural hazards weather observations and climate models. Seven key climatic parameters were selected: temperature, rainfall, drought, heat wave, flood, tropical cyclone, and sea level rise. Part two examined how the city functions, and pursues socio-economic development through a city vulnerability assessment. The qualitative, city vulnerability assessment was based on five sectors- people, infrastructure, environment, economy, and government. Each sector was analyzed extensively on a range of issues, and compared to other similar Chinese cities to more accurately judge its performances. Part three is the gap analysis. It was performed to understand the government actions and their effectiveness to respond to natural disasters, and whether the current and planned policies and programs address the current and future climate change impacts and natural disasters. This part was supported by the following inventories: inventory of natural disasters, and inventory of policies and programs. Part four therefore was to develop recommendations for each of the city vulnerability sectors. The 70 plus recommendations are specific to Ningbo's vulnerabilities and risks. They are described briefly, intended to serve as an introduction. Feasibility studies are recommended before further action or implementation.